Rhanterium suaveolens, Vitamin E and C Pretreatment Prevents Valproic Acid Induced Renal Oxidant Damage - Amrani, Amel; Benaissa, Ouahiba; Boubekri, Nassima; Benayache, Fadila; Benayache, Samir; Zama, Djamila (Natural Products Journal, The, 2021)
Background: Long-term administration of valproic acid (VPA) is known to promote renal tubular injury mediated by an increase in renal oxidative stress. Recent evidence indicates that natural antioxidants are alternative to attenuate oxidative stress and kidney damage. Objective: This study was performed to investigate the protective effects of n-butanol extract of Rhanterium suaveolens, vitamin E (Vit E), and vitamin C (Vit C) against VPA induced nephrotoxicity in mice. Methods: Mice were randomly divided into 6 groups (n: 8) and treated daily for 12 days. They received VPA (300 mg/kg intraperitoneally (ip)), buthanolic extract (100 mg/kg), Vit E (100 mg/kg), and Vit C (16.66 mg/kg) 1h prior to administration of VPA. On day 13, blood and Kidneys samples were analyzed for biomarker levels and histopathological changes. Kidneys homogenates were used for the determination of oxidative stress parameters that include malondialdehyde (MDA), glutathione (GSH) level and Glutathione Peroxidase (GPx) activity. Results: Treatment with VPA showed a significant increase in the levels of serum creatinine, urea and malondialdehyde (MDA) and decreasing the enzymatic activity (GPx) as well as GSH levels in the kidney with marked necrotic epithelial cells and infiltration in kidney sections as compared to the control group. Pretreatment with the n-butanol extract of R. suaveolens, Vit C or Vit E 1 h prior to administration of VPA showed a significant decrease in the levels of serum creatinine, urea, and MDA, as well as an improvement in the antioxidant elements and histological changes compared to those previously seen in the group treated with VPA alone. Conclusion: It is concluded that n-butanol extract of R. suaveolens, Vit C and Vit E pretreatment effectively improved renal function and tissue oxidative damage caused by VPA.
Keywords: oxidative stress